Influence of age in the adoption of new mobile payment systems - Liébana-Cabanillas, Francisco; Muñoz-Leiva, Francisco; Sánchez-Fernández, Juan (Review of Business Management, 2015)
Objective – The aim of this study is to propose and prove a theoretical integrative model which allows determining the relative importance of a new mobile payment system as well as the analysis of possible moderator effects of the age of its potential users within new electronic environments. Design/methodology/approach – To carry out this research, a web experiment based on a general population sample was conducted, in order to analyze the proposed model of behavior towards a new mobile payment system. Findings – Empirical results demonstrate that the suggested behavior pattern has an adequate adjustment showing that the age of users causes significant differences in the proposed connections between subjective rules and the facility of use and confidence, and again this last one in regard to the facility of use and the attitude toward that use. Practical implications – The conclusions and implications for management provide alternatives to consolidate this new business opportunity under the new technological developments. Originality/value – This paper is a pioneer study about the acceptance of mobile payment systems.